Undernotification and underreporting of tuberculosis in Zambia: a national data quality assessment - P. S. Lungu; M. E. Kabaso; R. Mihova; A. Silumesii; T. Chisenga; C. Kasapo; I. Mwaba; A. D. Kerkhoff; M. Muyoyeta; R. Chimzizi; K. Malama (BMC, 2022)
Abstract Background Despite national implementation of several high impact interventions and innovations to bolster tuberculosis (TB) detection and improve quality of TB services in Zambia, notifications have been declining since 2004. A countrywide data quality assessment (DQA) of Zambia's National TB and Leprosy Programme (NTLP) was undertaken to quantify the degree to which undernotification and underreporting of TB notifications may be occurring. Methods The NTLP conducted a retrospective DQA of health facilities in high burden districts in all ten Zambian provinces. Multiple routine programmatic data sources were triangulated through a multi-step verification process to enumerate the total number of unique TB patients diagnosed between 1st January and 31st August 2019; both bacteriologically confirmed and clinically diagnosed TB patients were included. Undernotification was defined as the number of TB patients identified through the DQA that were not documented in facility treatment registers, while underreporting was defined as the number of notified TB cases not reported to the NTLP. Results Overall, 265 health facilities across 55 districts were assessed from which 28,402 TB patients were identified; 94.5% of TB patients were ≥ 15 years old, 65.1% were male, 52.0% were HIV-positive, and 89.6% were a new/relapse case. Among all TB cases, 32.8% (95%CI: 32.2-33.3) were unnotified. Undernotification was associated with age ≥ 15 years old (adjusted prevalence odds ratio [aPOR] = 2.4 [95%CI: 2.0-2.9]), HIV-positive status (aPOR = 1.6 [95%CI: 1.5-1.8]), being a new/relapse TB case (aPOR = 17.5 [95%CI: 13.4-22.8]), being a clinically diagnosed TB case (aPOR = 4.2 [95%CI:3.8-4.6]), and being diagnosed at a hospital (range, aPOR = 1.5 [95%CI: 1.3-1.6] to 2.6 [95%CI: 2.3-2.9]). There was substantial heterogeneity in the proportion of unnotified TB cases by province (range, 18.2% to 43.6%). In a sub-analysis among 22,199 TB patients with further data available, 55.9% (95%CI: 55.2-56.6) were notified and reported to the NTLP, 32.8% (95%CI: 32.2-33.4) were unnotified, and 11.3% (95%CI: 10.9-11.7) went unreported to the NTLP. Conclusions The findings from Zambia's first countrywide TB programme DQA demonstrate substantial undernotification and underreporting of TB cases across all provinces. This underscores the urgent need to implement a robust and integrated data management system to facilitate timely registration and reporting of all TB patients who are diagnosed and treated.